The “euro effect” and Outward Foreign Direct Investment - Tchorek, Grzegorz; Brzozowski, Micha (Revista de Economía Mundial, 2017)
The "euro effect" is an important phenomenon in the debate on monetary in-tegration results in Europe. While in the existing literature the impact of the euro adoption is usually studied on trade data, the main goal of the paper is to examine whether the "euro ef-fect" can be detected in Outward Foreign Direct Investment (OFDI) flows from the OECD countries. Our approach is justified by the fact that trade and FDI are interconnected and both can be used as an internationalization strategy. Using the difference-in-differences method and the gravity equation corrected for the sam-ple selection and firm-heterogeneity biases, we investigate the trends of the strength of the impact of the euro over the 1985-2012 period. Our results suggest that the ’euro effect’ is positive, is not time invariant and does not display a clear trend. It was the strongest in the years 2007 and 2008 and insignificant shortly after its introduction and during the global fi-nancial and European fiscal crises.